A survey of nurse informatics competencies of professional nurses in clinical practice public hospitals in South Africa - Loretta le Roux; Million Bimerew; Jennifer-Anne Chipps (Elsevier, 2024)
Background: Competence in nursing informatics is vital for efficient nursing care in today's technologically-enabled healthcare environment. In South Africa little is known on the competence of professional nurses in clinical practice in nursing informatics. Objectives: The study examined the self-rated competence in nursing informatics among professional nurses practicing in clinical settings at two hospitals in the Western Cape, South Africa. Method: A cross-sectional descriptive survey was conducted with 205 professional nurses from two public hospitals in the Cape Metropole, Western Cape. The study participants completed the TANIC© scale, a self-administered nursing informatics questionnaire. Descriptive analysis was done for demographic variables and activities, with mean scores out of 4, interpreted based on the novice (1), advanced beginner (2), comfortable (3), and proficient (4) ratings. Confidence intervals were calculated for all nursing informatics competencies in the domains of computer literacy, clinical information management and information literacy and their sub-domains. Results: The respondents rated the computer literacy domain significantly higher than the other two domains (2.63/4 [95 %CI 2.5-2.76]), with average ratings approaching the 'comfortable' competency range. This was followed by clinical information management (2.09/4 [95 %CI 1.95-2.23]), and information literacy (2.05/4 [95 %CI 1.92-2.17]), with average ratings located in the 'novice' to 'advanced beginner' competency range. Conclusion: The study showed that practicing nurses have a limited level of nursing informatics competence, especially in the domains of clinical information management and information literacy. These findings support the need for educational programmes to extend beyond basic computer skills and prioritize continuous professional development in nursing informatics.